Epidermolysis bullosa: a tale of two sisters - Patil, Tanvi; Shinde, Rajendra (International Journal of Research in Dermatology, 2023)
Epidermolysis bullosa (EB) is a clinically and genetically heterogenous, inherited, mechanobullous disorder characterised by spontaneous or trauma induced blisters over skin and mucous membranes. Four major forms are: EB Simplex, EB Junctional, EB dystrophic and mixed. A 11-year-old and a 9 year old female child, both sisters, accompanied by their father, presented to dermatology OPD, with chief complaints of multiple raw areas over elbows and knees since infancy. There was history of fluid filled lesions which were induced by trauma or friction during handling or while playing. These lesions ruptured on their own or on trauma to form raw areas with crusting which further healed with scarring and small white raised lesions. Also, he gave history of loss of nails following blistering on toes in infancy. No associated systemic complaints were noted. On examination, both of them presented with multiple erosions and ulcers with oozing of blood, few bullae and crusted lesions over elbows, knees and feet. There were multiple atrophic scars and skin coloured to whitish papules [milia] over feet, ankles, elbows and knees. There were loss of nails of toes of both feet. On biopsy, histopathological examination revealed bullae at dermoepidermal junction. Diagnosis of EB junctional was made. EB is a rare inherited disorder. Its management includes prevention and healing of blisters and infection. Psychological support to patients and their families is of prime importance.